Probing the Outer Mitochondrial Membrane in Cardiac Mitochondria with Nanoparticles - Salnikov, V. (Biophysical Society, 2007)
The outer mitochondrial membrane (OMM) is the last barrier between the mitochondrion and the cytoplasm. Breaches of OMM integrity result in the release of cytochrome c oxidase, triggering apoptosis. In this study, we used calibrated gold nanoparticles to probe the OMM in rat permeabilized ventricular cells and in isolated cardiac mitochondria under quasi-physiological ionic conditions and during permeability transition. Our experiments showed that under control conditions, the OMM is not permeable to 6-nm particles. However, 3-nm particles could enter the mitochondrial intermembrane space in mitochondria of permeabilized cells and isolated cardiac mitochondria. Known inhibitors of the voltage-dependent anion channel (VDAC), König polyanion, and 4,4′-diisothiocyanatostilbene-2,2′-disulfonic acid inhibited this entrance. Thus, 3-nm particles must have entered the mitochondrial intermembrane space through the VDAC. The permeation of the isolated cardiac mitochondria OMM for 3-nm particles was ∼20 times that in permeabilized cells, suggesting low availability of VDAC pores within the cell. Experiments with expressed green fluorescent protein showed the existence of intracellular barriers restricting the VDAC pore availability in vivo. Thus, our data showed that 1), the physical diameter of VDAC pores in cardiac mitochondria is ≥3nm but ≤6 nm, and 2), permeability transition-related mitochondrial swelling results in breaching and disruption of the OMM.